Strategies Proposal for the Educational Administration of Thai Language at Singapore International School, Chiang Mai, Functioning Under the Auspices of the Office of the Private Education Commission - Moomak, Sunantha; Somsathan, Prapatsorn (An Online Journal of Education, 2024)
The research aims to: 1) Study the necessary requirements of the proposed strategic teaching management approach for the Thai language curriculum group at an international school in Chiang Mai, Singapore. 2) Develop a strategic teaching management approach for the Thai language curriculum group. 3) Evaluate the suitability and feasibility of the proposed teaching management strategy for the Thai language curriculum group at the international school in Chiang Mai, Singapore. The research population consists of the school director, expert instructor, teacher and parents. The research tools used are in-depth interviews and an assessment form for the (draft) guidelines. The statistical analysis includes percentages, mean values, standard deviations, Modified Priority Needs Index (PNIModified), and content analysis. The research findings are as follows: 1) The necessary requirements of the proposed strategic teaching management approach for the Thai language curriculum group at the International School in Chiang Mai, Singapore, consist of six aspects, including (1) Mission, objectives, and strategies of the organization, (2) Situation analysis, (3) Identifying opportunities and obstacles, (4) Analyzing organizational resources and capabilities, (5) Identifying strengths and weaknesses, and (6) Strategic planning, all at a high level. 2) The strategic teaching management approach for the Thai language curriculum group at the International School in Chiang Mai, Singapore, comprises five components, 25 guidelines. 3) The proposed strategic teaching management approach for the Thai language curriculum group at the International School in Chiang Mai, Singapore, is highly feasible and suitable.